Level of Hand Hygiene Compliance and Its Associated Factors Among Health Care Workers at Eka Kotebe General Hospital, Addis Ababa, Ethiopia - Muluken Tadesse; Alebachew Shimelash; Eniyew Tegegne (SAGE Publishing, 2022)
Background: Poor hand hygiene is an important source of infection, but maintaining hand hygiene is the most important measure to prevent infections. Hand hygiene compliance and its associated factors are not well recognized in Ethiopia. Therefore, this study was intended to determine hand hygiene compliance and its associated factors among health care workers in Eka Kotebe General Hospital. Methods: A cross-sectional study was conducted among health care workers at Eka Kotebe General Hospital. A self-administered questionnaire supplemented by a World Health Organization Hand Hygiene Technical Reference Manual was used to collect data. Data was entered using Epi Info 7.2.0.1 and exported to SPSS 23 for analysis. The data were analyzed using descriptive and inferential statistics. Statistical significance was determined using a P -value of ⩽.05 with a 95% confidence interval. Results: Hand hygiene compliance among healthcare workers was 22.2%. Hand hygiene training (AOR = 2.9, 95% CI: 1.13-7.52), presence of hand hygiene indication poster (AOR = 3.38, 95% CI: 1.18-9.66), hand hygiene promotion by IPC team (AOR = 4.2, 95% CI: 2.53-8.58)), working experience ⩾5 years of a health care providers (AOR = 3.96, 95% CI: 1.12-13.9), being midwife (AOR = 17.1, 95% CI: 2.8-10), being nurse (AOR = 5.3, 95% CI: 2.09-7.8) by profession, and presence of water (AOR = 2.50, 95% CI: 2.20-11.78) were significantly associated factors to hand hygiene compliance. Conclusion: The level of hand hygiene compliance among health care providers was found to be low. Training about hand hygiene, the presence of hand hygiene indication posters, hand hygiene promotion by the IPC team, working experience of health care providers, being a nurse and midwife, and the presence of water were independent predictors of hand hygiene compliance. Health care workers need to be given training on hand hygiene as well as hand hygiene facilities shall be installed and supplied by the hospital in a sustained manner.